Advanced Materials, Structures and Processing Technologies Based on Pulsed Laser - Rong, Youmin; Wu, Congyi; Huang, Yu (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Pulsed lasers are lasers with a single laser pulse width of less than 0.25 s, operating only once in every certain time interval. Commonly used pulsed lasers are nanosecond, femtosecond, and picosecond lasers. A pulsed laser produces short pulses with a short interaction time with the material, which can largely avoid impact on the thermal movement of molecules and has a minimal thermal impact on the surrounding materials, thus having significant advantages in precision microfabrication. It is now widely used in flexible electronics, chips, medicine, and other fields, such as photographic resin curing, microwelding, vision correction, heart stent manufacturing, etc. However, as an emerging processing technology, the application prospects of pulsed lasers have yet to be fully expanded, and there is still a need to continuously explore the mechanisms of interaction with materials, to manufacture advanced functional structures, and to develop advanced process technologies.